2020
DOI: 10.4103/jehp.jehp_102_20
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the relationship between attachment styles and somatic symptoms with the mediating role of emotional processing

Abstract: INTRODUCTION: In spite of our general knowledge about psychological roots and defects of developmental processes in the formation of somatic symptoms, the effect of the interaction of developmental components with cognitive-emotional variables is unclear. Previous researches suggest that individuals with insecure attachment may have a higher risk to experience of somatic symptoms. The main aim of this study is “Modeling the Relationship between Attachment Styles and Somatic Symptoms with the Media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Individuals with avoidance issues, anxiety, and attachment insecurity are prone to physiological health risks. Anxious and insecure attachment styles have been linked to higher stress perceptions and reactivity, as well as a positive association between hypochondriacal and somatic symptoms (Dolatshahi et al 2020;Taylor et al 2012). Studies have shown that an anxious attachment style has been linked to health anxiety (Gozan and Menaldi 2020) and a variety of inflammation-driven cardiovascular diseases (CVD), including stroke, heart attack, high blood pressure, and increased chronic illness (Pietromonaco and Beck 2019;Oladi and Dargahi 2018;McMahon et al 2021;Michal and Beutel 2021).…”
Section: Correlated Health Risks and Substantiating Comorbiditymentioning
confidence: 99%
“…Individuals with avoidance issues, anxiety, and attachment insecurity are prone to physiological health risks. Anxious and insecure attachment styles have been linked to higher stress perceptions and reactivity, as well as a positive association between hypochondriacal and somatic symptoms (Dolatshahi et al 2020;Taylor et al 2012). Studies have shown that an anxious attachment style has been linked to health anxiety (Gozan and Menaldi 2020) and a variety of inflammation-driven cardiovascular diseases (CVD), including stroke, heart attack, high blood pressure, and increased chronic illness (Pietromonaco and Beck 2019;Oladi and Dargahi 2018;McMahon et al 2021;Michal and Beutel 2021).…”
Section: Correlated Health Risks and Substantiating Comorbiditymentioning
confidence: 99%
“…Esta diferenciación entre CERS adaptativas y desadaptativas se basa en cómo dichas estrategias ayudan a la persona a regular de manera eficaz y consciente sus emociones tras un evento negativo (Jermann et al, 2006). Estudios como el de Ellard et al (2017) han señalado que el uso de CERS desadaptativas está directamente relacionado con mayores niveles de ansiedad y somatizaciones, y algunas CERS como la rumiación o la preocupación se ha relacionado de forma directa y positiva con los síntomas de ansiedad y somatización (Aldao et al, 2010;Falahatdoost et al, 2020;McEvoy et al, 2013;Schnabel et al, 2022;Tang & Thomas, 2020). Asimismo, el uso disfuncional de estrategias como la metacognición, la conciencia sobre nuestros propios pensamientos, puede llevar a sesgos atencionales dirigidos hacia la amenaza y generar un mayor empleo de las CERS desadaptativas, llevando así a mayores niveles de ansiedad y síntomas somáticos (Wells & Matthews, 2014).…”
Section: Introductionunclassified
“…Despite EAET's effectiveness, little is known about the mechanisms by which EAET achieve its effects. In theory, emotional processing is a key mechanism (Lumley and Schubiner, 2019), as deficits in emotional processing have been identified in patients with chronic pain and IBS (Baker et al, 2010;Esteves et al, 2013;Phillips et al, 2013;Gay et al, 2019), and problems in emotional processing have been found to mediate the association between childhood adversity and the development of psychiatric (Chung and Chen, 2017) and somatic symptoms (Mozhgan et al, 2020). Facets of emotional processing, such as emotional differentiation, naming, experiencing, tolerating, and expression, are believed to be a core mechanism in psychodynamic treatments of certain conditions (Messer, 2013;Høglend and Hagtvet, 2019).…”
Section: Introductionmentioning
confidence: 99%